Medicinal and Nutritional Analysis of Fig (Ficus Carica) Seed Oil; A New Gamma Tocopherol and Omega-3 Source - Kucukerdonmez, Ozge; Baygeldi, Nefise; Akder, Rana Nagihan; Çağındı, Özlem (Progress in Nutrition, 2021)
Ficus carica (common fig) is a tree native to southwest Asia and the eastern Mediterranean and is among the first plants cultivated by humans. Fig harvest is of worldwide importance for their dry and fresh consumption. The fruit, roots, and leaves of figs are used as anti-inflammatory and antispasmodic drugs for treating various disorders such as gastrointestinal (colic, dyspepsia, anorexia, and diarrhea), respiratory (a sore throat, cough, and bronchial problems) and cardiovascular disorders in traditional medicine. Previous studies have reported the use of latex, leaves, fruit, and root of the fig in the literature. However, so far, fig seeds (Ficus carica) have not been decomposed and analyzed for their oil content. High-Performance Chromatography Fluorescence Detector (HPLC-FLD) method was used to measure the level of vitamin E tocopherol, and the fatty acid content was analyzed with Gas Chromatography with Flame Ionization Detector (GC-FID) method. The results showed that Ficus carica seed oil is a rich source of linolenic acid (C18:3), linoleic acid (C18:2) and oleic acid (C18:1). Besides, it contains 314.61±51.53 mg/100 g gamma tocopherol. Thus, Ficus carica seed oil is of importance in the health sciences.